Analisis Manajemen Kelas Dalam Meningkatkan Hasil Belajar Siswa - Husrin Konadi; Abdul Marif (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2021)
This study aims to analyze classroom management in improving student learning outcomes. The type of research carried out is qualitative research, with a descriptive approach and the sampling in this study uses purposive sampling, where the sample is taken based on certain meanings and objectives, so that the sample in this study was 30 students of class II MIN 10 Central Aceh. The results of this study indicate an increase in learning outcomes after classroom management is carried out. From the results above, it can be seen that there is an increase after being given class management. In the very low category, it shows that there is 1 person who has very low learning outcomes or as much as 3.5%, while after being given class management there is no very low category. Then in the low category there are 8 people or as many as 26.6% who have low learning outcomes and after being given class management there is only 1 person who has a low category of learning outcomes. Meanwhile in the medium category there are 33.3% or 10 people who have the moderate category before class management is carried out, and after class management is carried out there are 40% or as many as 12 people who have the medium category of learning outcomes. In the high category before class management was carried out there were 6 people or as many as 20% who had good learning outcomes, after the high category class management there were 10 people or 33.3% who had good learning outcomes. In the very high category there are 5 people or as many as 16.6% who have good learning outcomes, and after being given class management there are 7 people or as many as 23.3% who have very high learning outcomes categories. Thus there is an increase between before being given class management and after being given class management